2019
DOI: 10.1155/2019/6307035
|View full text |Cite
|
Sign up to set email alerts
|

Female Patients with Dermatitis Herpetiformis Show a Reduced Diagnostic Delay and Have Higher Sensitivity Rates at Autoantibody Testing for Celiac Disease

Abstract: Objective. Our objective was to characterize the demographic information, clinical features, and laboratory data of patients with dermatitis herpetiformis (DH). Methods. In this multicentre cross-sectional study, consecutive patients with a new diagnosis of DH that referred to nine di erent Italian centers between 2011 and 2016 were characterized assessing demographic, clinical and laboratory ndings, and evaluating gender and age di erences across selected variables. Results. A total of 151 patients were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…There have been only a few studies addressing the differences between males and females affected by DH, and the main focus has been on newly diagnosed patients. Previous studies have linked male sex with younger age at the onset of DH symptoms, more severe skin symptoms at diagnosis and more frequent initiation of dapsone after diagnosis ( 28 30 ). Furthermore, 2 studies have shown an increased risk for delayed diagnosis in females ( 21 , 29 ), but, in contrast, 1 study associated increased diagnostic delay with male sex ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few studies addressing the differences between males and females affected by DH, and the main focus has been on newly diagnosed patients. Previous studies have linked male sex with younger age at the onset of DH symptoms, more severe skin symptoms at diagnosis and more frequent initiation of dapsone after diagnosis ( 28 30 ). Furthermore, 2 studies have shown an increased risk for delayed diagnosis in females ( 21 , 29 ), but, in contrast, 1 study associated increased diagnostic delay with male sex ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prime example of this is found in a peer-reviewed study that analyzed the sensitivity rates of autoantibody testing for celiac disease for the two sexes. 17 For the data collection of the results of the colonoscopies corresponding with the positive Cologuard tests, a medical record database was used to find a sample. Permission was granted by a northeast Ohio local hospital to find all of its positive Cologuard results within the last three years in order to target an initial sample of at least 100 participants.…”
Section: Methodsmentioning
confidence: 99%
“…20 Several studies investigated anti-deamidated gliadin antibodies in DH showing that they have in general a slightly higher sensitivity and a slightly lower specificity than anti-TG2 antibodies in patients with DH. [74][75][76][77][78][79] Thus, detection of antibodies against deamidated gliadin may be considered in the diagnostic workup for DH, but such assays are not recommended as primary tests.…”
Section: Test Requirementsmentioning
confidence: 99%